Pengaruh Penambahan POC Ampas Teh terhadap Pertumbuhan dan Hasil tanaman pakcoy (Brassica rapa L.) Secara Hidroponik Sistem Sumbu - Butar, Adril Persada Butar; Pradnyawathi, Ni Luh Made; Wijana, Gede (Agrotrop : Journal on Agriculture Science; Vol 14 No 2 (2024), 2024)
The Effect of Additioning Tea Waste LOF on Growth and Products of Pakcoy ( Brassica rapa  L.) Plants by Wick System Hydroponic. Pakcoy ( Brassica rapa  L.) is one of the vegetables that can be cultivated using a hydroponic system. The wick hydroponic system is one of the hydroponic techniques used in vegetable cultivation, involving the use of standing water in the installation and passive flow circulation. The nutrients commonly used in hydroponic cultivation are the AB Mix nutrient solution. However, the use of liquid organic fertilizer (LOF) in hydroponic vegetable cultivation is an important consideration to reduce the use of inorganic fertilizers. The research objective is to determine the growth response of pakcoy cultivation with the addition of tea waste LOF, which contributes to the growth and yield of pakcoy plants. This study utilized a Completely Randomized Design (CRD) with six levels, namely 0 ml/L, 2 ml/L, 4 ml/L, 6 ml/L, 8 ml/L, and 10 ml/L, each with four replications. The research was conducted in the Experimental Greenhouse and Agronomy and Horticulture Laboratory, Faculty of Agriculture Udayana University from February to May 2023. The treatment of 10 ml/L was found to be the best concentration for the addition of tea waste LOF in promoting the growth and yield of pakcoy plants in the wick hydroponic system. The results of the regression analysis for fresh canopy weight and oven dry canopy weight have not revealed an optimal concentration. This is due to the presence of a positive linear relationship with the concentration of tea waste LOF, indicating that both weights will increase with an increase in concentration.